Racial Justice and Social Justice in The Indian Revolution - Pedoni, Octavio Marino (2025)
This article explores the relationship between racial justice and social justice in the context of Fausto Reinaga’s work, The Indian Revolution (1970). Reinaga’s critique underlines the need for a radical transformation of social structures to achieve true justice. This article uses a Latin American historicist perspective to argue that social justice cannot be fully achieved without racial justice, which would recognize and value the contributions of Indian subjects, in this particular case. Also, the figure of Túpac Amaru is considered as a precursor of social justice, offering a model to address the structural inequalities of Latin American societies.